If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2c + 5)(c + 4) = 0 Reorder the terms: (5 + 2c)(c + 4) = 0 Reorder the terms: (5 + 2c)(4 + c) = 0 Multiply (5 + 2c) * (4 + c) (5(4 + c) + 2c * (4 + c)) = 0 ((4 * 5 + c * 5) + 2c * (4 + c)) = 0 ((20 + 5c) + 2c * (4 + c)) = 0 (20 + 5c + (4 * 2c + c * 2c)) = 0 (20 + 5c + (8c + 2c2)) = 0 Combine like terms: 5c + 8c = 13c (20 + 13c + 2c2) = 0 Solving 20 + 13c + 2c2 = 0 Solving for variable 'c'. Factor a trinomial. (4 + c)(5 + 2c) = 0Subproblem 1
Set the factor '(4 + c)' equal to zero and attempt to solve: Simplifying 4 + c = 0 Solving 4 + c = 0 Move all terms containing c to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + c = 0 + -4 Combine like terms: 4 + -4 = 0 0 + c = 0 + -4 c = 0 + -4 Combine like terms: 0 + -4 = -4 c = -4 Simplifying c = -4Subproblem 2
Set the factor '(5 + 2c)' equal to zero and attempt to solve: Simplifying 5 + 2c = 0 Solving 5 + 2c = 0 Move all terms containing c to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2c = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2c = 0 + -5 2c = 0 + -5 Combine like terms: 0 + -5 = -5 2c = -5 Divide each side by '2'. c = -2.5 Simplifying c = -2.5Solution
c = {-4, -2.5}
| 7+3y=18+x | | 3e-x-1=5 | | -16x^2+80= | | log(y)=1.9747log(x) | | 69x+9y=900 | | y=x^2+49 | | 6z-12z=1-18 | | 11n+9=6n+44 | | (9*4)-5=9*(4-5) | | -6h+4=-10h+16 | | 10p(4/5p) | | 5x+10-3x-3= | | y=4x^2+12x-5 | | -8x-18=-146 | | 4t-2=6t+6 | | -16x^2+80x= | | -5x*2x= | | x=1.8*x+32 | | 2x+14=-6x+34 | | a(n)=12+(n-1)(3) | | -6h+4=-10h+6 | | log(6x+12)=1+log(x-6) | | -2-y=-8(2+y) | | X*4+200=x*14-20 | | 50-10(x-5)= | | 6=30-8x | | 4(6v-1)(v-4)=0 | | F(x)=4x^2+32x | | 2x=55 | | 6u=3u+45 | | y*(2)*(-3)=30 | | 10*3x= |